Metagenomic next-generation sequencing confirms the diagnosis of Legionella pneumonia with rhabdomyolysis and acute kidney injury in a limited resource area: a case report and review - Du, Rao; Feng, Yinhe; Wang, Yubin; Huang, Jifeng; Tao, Yuhan; Mao, Hui (Frontiers in Public Health, 2023)
Background Legionella pneumonia, rhabdomyolysis, and acute kidney injury are called the Legionella triad, which is rare and associated with a poor outcome and even death. Early diagnosis and timely treatment are essential for these patients. Case presentation A 63-year-old man with cough, fever, and fatigue was initially misdiagnosed with common bacterial infection and given beta-lactam monotherapy but failed to respond to it. Conventional methods, including the first Legionella antibody test, sputum smear, and culture of sputum, blood, and bronchoalveolar lavage fluid (BALF) were negative. He was ultimately diagnosed with a severe infection of Legionella pneumophila by metagenomics next-generation sequencing (mNGS). This patient, who had multisystem involvement and manifested with the rare triad of Legionella pneumonia, rhabdomyolysis, and acute kidney injury, finally improved after combined treatment with moxifloxacin, continuous renal replacement therapy, and liver protection therapy. Conclusion Our results showed the necessity of early diagnosis of pathogens in severe patients, especially in Legionnaires' disease, who manifested with the triad of Legionella pneumonia, rhabdomyolysis, and acute kidney injury. mNGS may be a useful tool for Legionnaires' disease in limited resource areas where urine antigen tests are not available.